The effects of mepiquat chloride (DPC) on the soluble protein content and the activities of protective enzymes in cotton in response to aphid feeding and on the activities of detoxifying enzymes in aphids - Quan-Cheng Zhang; Xiao-Xia Deng; Jun-Gang Wang (BMC Plant Biology, 2022)
Abstract Background Mepiquat chloride (DPC) enhances the resistance of cotton plants, and it is widely used as a growth regulator. DPC can stimulate photosynthesis, stabilize the structure of cotton leaves, and affect population reproduction and energy substances in Aphis gossypii Glover (cotton aphids), but interactions between DPC and cotton aphids remain unclear. In this study, we analyzed the physiological responses of cotton to DPC, and the toxicity of DPC toward cotton aphids, before and after feeding, to explore the DPC-induced defense mechanism against cotton aphids. Results Measurements of protective enzyme activity in cotton showed that the soluble protein contents, peroxidase (POD) activity, and catalase (CAT) activity in cotton treated with different concentrations of DPC were higher than in the control. Superoxide dismutase (SOD) activity was higher than that of the control when the concentration of DPC was < 0.1 g/L. Under aphid feeding stress, POD activity in cotton treated with a low insect population density was significantly lower than in the controls, but the reverse was true for cotton treated with a high insect population density, and SOD activity was positively correlated with population density. The activities of detoxification enzymes in field and laboratory experiments showed that DPC promoted the specific activity of glutathione S-transferase (GST) in cotton aphids, while the specific activities of carboxylesterase (CarE) and acetylcholinesterase (AchE) were decreased. Conclusions DPC enhanced the aphid resistance in cotton by increasing the soluble protein content and the activity of protective enzymes. It also had a toxic effect on cotton aphids by increasing GST activity (the main DPC target). DPC increased the soluble protein content and protective enzymes activity in cotton under aphid stress, and thereby enhanced tolerance to cotton aphids. It conclude that DPC interferes with cotton aphids through indirect (DPC induced cotton defense responses) and direct (DPC toxicity to cotton aphids) ways, which plays a positive role in interfering with cotton aphids.